2019
DOI: 10.15414/jmbfs.2019.8.5.1130-1134
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of "Biofloc" Aquatic System for Polyculture With Tilapia (Oreochromis Sp.) and River Prawn (Macrobrachium Sp.)

Abstract: Aquaculture is a productive activity in economic growth due to market productivity which supports many Ecuadorian communities. However, exotic species has been the basis of this activity without considering the endemic and mega-diverse component of Ecuador. On the other hand, current aquaculture systems use a lot of water, generating discharge of nitrogen and phosphorus, causing a negative impact on natural watersheds. The present investigation focused on the diversification of aquaculture production and envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Biofloc-based systems often consist of various live and dead plankton species, and in this study, ciliates, rotifers and nematodes were identified and quantified. These zooplankton groups increased in abundance with increasing C-N ratios, which is in agreement with other studies (Asaduzzaman et al, 2010;Gallardo-Collí et al, 2019;Manan et al, 2017;Reinoso et al, 2019).…”
Section: Water Quality Variablessupporting
confidence: 93%
See 1 more Smart Citation
“…Biofloc-based systems often consist of various live and dead plankton species, and in this study, ciliates, rotifers and nematodes were identified and quantified. These zooplankton groups increased in abundance with increasing C-N ratios, which is in agreement with other studies (Asaduzzaman et al, 2010;Gallardo-Collí et al, 2019;Manan et al, 2017;Reinoso et al, 2019).…”
Section: Water Quality Variablessupporting
confidence: 93%
“…After 20 days, 50 ml water samples were collected from each tank to determine the zooplankton communities. The samples were preserved in 4% buffered formalin (Emerenciano et al, 2013;Thompson et al, 2002), and 1 ml was placed on Sedgwick-Rafter counting cell (Azim & Little, 2008), and the amount of ciliates, rotifers and nematodes were identified and counted (Gallardo-Collí et al, 2019;Hosain et al, 2013;Manan et al, 2017;Reinoso et al, 2019;Santhanam et al, 2019;Smith, 2001) A total 300 fields of SR-cells were counted for each sample in triplicate for each tank.…”
Section: Zooplankton Compositionmentioning
confidence: 99%
“…The recommended C:N range to promote biofloc formation is from 11 to 20:1 (Ebeling et al 2006;Avnimelech 2012;Pérez-Fuentes et al 2016). Some studies used 15:1 C:N ratio (Kasan et al 2018;Cang et al 2019) while others adapted the maximum recommended ratio of 20:1 (de Souza et al 2019;Reinoso et al 2019). In practice, up to 20:1 is the recommended C:N ratio on the first three months of culture followed by a reduction to around 15:1 at the latter part of the culture to manage the decline of pH and production of settled biomass (Pérez-Fuentes et al 2016).…”
Section: Experimental Designmentioning
confidence: 99%